Do the predators of Yamal have a learning effect of artificial nests? - Olsen, Dag Alexander Hultgren (UiT Norges arktiske universitet, 2020)
Many artificial nest studies that goes over several years place the nests in the same location each placement. Over the years there is a chance that the predators learn where the nests are placed and that can give skewed results. The goal of my study is to see if the predators learn where the nests are located. This was done over three study sites on the Yamal peninsula. In two of the study sites the nests were placed over 4 years with an early and late incubation timing. The last study site had 2 years and only one placement each year. Each time the nests were placed half of the nests where covered nests while the rest was uncovered. The results were tested using glmer in R. The results show an increase in predation over the years. The results also show a difference between the early and late incubation timing, but this difference decreased over the years. The increase over the years suggests that the predators do learn where the nests are placed each year since more nests are predated each year. The difference between the early and late predation of nests might be caused by the shift in search image for the predators, but the decrease in this difference suggests that the learning effect over the years negate this shift. Overall there is an indication that there is a learning effect for the predators and should be taken into consideration when using multiannual artificial nests.